Study Of Urban Area Development: Consistency Of Urban Policy And :Planning Based On Local Wisdom Of The Dayak Tribe - M. Riban Satia; Irwani Irwani; Nova Riyanti; Desy Selawaty; Sirajul Rahman; Ezio Marra (LPPM Universitas PGRI Sumatera Barat, 2024)
The city of Palangka Raya has 3 faces, namely the city face, the village face and the forest face. The rapid development of the Palangka Raya City area will certainly change every face. The basic idea of this study stems from anxiety in observing the existence of local wisdom which is starting to be eroded by developments over time. Sometimes local wisdom is considered old-fashioned and uninteresting, but this is different from the Dayak tribe, which still has a strong culture. So the urgency of this research problem is to examine the complexity of the development of urban areas which will certainly sacrifice many aspects of forests to become urban areas. Seeing that this problem is multi-faceted, researchers dissect it from the perspective of policy, planning and consistency of sustainable development based on local wisdom. This research aims to investigate the existence of local Dayak wisdom in urban policy and planning in Palangka Raya City. As well as analyzing the consistency of government responsibility for the development of Palangka Raya City. This research uses a design that adopts qualitative research methods. The research approach does not focus on government governance and its implementation, but attempts to find answers to the study through the theory used as an analytical tool, namely CIPP model policy evaluation. The research results show that the existence of local wisdom of the Dayak Tribe in urban area policy in Palangka Raya is quite significant, however, consistency in urban planning based on local wisdom of the Dayak Tribe in Palangka Raya is still going through various dynamics and maintaining it is a challenge